Microencapsulation of purified amylase enzyme from pitaya (Hylocereus polyrhizus) peel in Arabic gum-chitosan using freeze drying - Amid, Mehrnoush; Abd Manap, Mohd Yazid; Ahmad Zohdi, Nor Khanani (MDPI, 2014)
Amylase is one of the most important enzymes in the world due to its wide application in various industries and biotechnological processes. In this study, amylase enzyme from Hylocereus polyrhizus was encapsulated for the first time in an Arabic gum-chitosan matrix using freeze drying. The encapsulated amylase retained complete biocatalytic activity and exhibited a shift in the optimum temperature and considerable increase in the pH and temperature stabilities compared to the free enzyme. Encapsulation of the enzyme protected the activity in the presence of ionic and non-ionic surfactants and oxidizing agents (H₂O₂) and enhanced the shelf life. The storage stability of amylase is found to markedly increase after immobilization and the freeze dried amylase exhibited maximum encapsulation efficiency value (96.2%) after the encapsulation process. Therefore, the present study demonstrated that the encapsulation of the enzyme in a coating agent using freeze drying is an efficient method to keep the enzyme active and stable until required in industry.